Civil Engineering Master?s Programs: A Comprehensive Review of Types and Requirements And A Review and Update of CEE 498: Construction Project Management - Rogers, Joshua (My University, 2011)
The purpose of this report was to describe the range of existing civil engineering master?s programs by providing fundamental and statistical information on domestic ABET accredited civil engineering master?s programs. With such a diverse range of available programs, misinformation is commonplace in regards to the available programs to fulfill further education in a master?s degree format in civil engineering. A full version of this report can be found in Appendix 1. Researched and written by Tom Lennox (ASCE), Dion Coward (ASCE), Jeff Russell (UW-Madison), and Josh Rogers (UW-Madison), a comprehensive database of available master?s programs and specializations was compiled. Surveys were sent to department head?s via the ASCE Department Head Listserve on November 2, 2010. This listserve contains 227 institutions, 41 of which have baccalaureate-level programs online, leaving 186 institutions with master?s programs. Our total response of 121 institutions results in a response rate of 65%. For these responses, 232 individual programs were reported. For clarification purposes, Schools and Universities are referred to as institutions and individual degrees are referred to as ?Programs.?